The Effect of Creativity and Work Motivation on the Productivity of Islamic Religious Education Teachers - Hermilia Hermilia; Nur Ahyani; Alhadi Yan Putra (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
The effect of creativity and work motivation on the productivity of Islamic Religious Education (IRE) teachers. This study aims to determine the effect of creativity and work motivation on the productivity of IRE teachers in Lengkiti district at Ogan Komering Ulu (OKU) district. As for the formulation of the problem, (1) is there an effect of creativity on the productivity of IRE elementary school teachers?, (2) is there an effect of motivation on the productivity of IRE elementary school teachers?, and (3) is there an effect of creativity and motivation on the productivity of IRE elementary school teachers?. This type of research is descriptive. The sample in this study amounted to 19 people in 19 SD Negeri in OKU District. Data collection techniques in the form of observation, questionnaires and documentation. The results of this study. Based on respondents' perceptions about the effect of creativity on teacher productivity in a moderate category, the mean was 69.43. The results of the descriptive analysis of the effect of IRE motivation on teacher productivity are in a good category, the mean is 58.68. The results of the analysis of the effect of creativity and work motivation on teacher productivity are in moderate category with a mean of 49.59.